Isolation, Purification and Identification of Curcuminoids from Turmeric (Curcuma longa L.) by Column Chromatography - Antony2, S. Revathy1, S. Elumalai1*, Merina Benny (Journal of Experimental Sciences, 2011)
Turmeric, curcuma longa L of Zingiberaceae family is a widely cultivated spice in India and other Asian countries. Turmeric is rich in curcuminoids, and recognized for their broad spectrum of biological activities, curcuminoids vary in chemical structures, physico-chemical characteristics as well as the functional properties. This study focused on screening of solvents for extraction of curcuminoids, isolation and purification of curcuminoids by column chromatography followed by purity analysis by HPLC. Different solvents were used for extraction, among them acetone showed maximum yield of each curcuminoids. Various solvent at different polarity were pre-tested in TLC for separation of curcuminoids, chloroform:methanol at 95:5 showed better resolution of Rf value at 0.75, 0.55, 0.27, as Curcumin(C), Demethoxycurcumin(DMC), Bisdemethoxycurcumin(BDMC) respectively. The acetone extract was subjected to silica gel column chromatography with chloroform: methanol at increasing polarity. Yield of each curcuminoid from column was determined and total curcuminoids of individual fractions of each curcuminoids were determined by UV spectrophotometry. Crystallization of each compound was done using chloroform: methanol (5:2) at 5°C. The isolated curcuminoids (C, DMC, and BDMC) showed single peaks at retention times of 10.81, 12.79, 13.03 min respectively on HPLC.